Effects of incubation temperature on muscle morphology and growth in the pacu (Piaractus mesopotamicus) - de Assis, JMF; Carvalho, R. F.; Barbosa, L.; Agostinho, Claudio Angelo [UNESP]; Dal Pal-Silva, M. (Elsevier B.V., 2004)
This study describes the influence of incubation temperature during initial development phase on the morphology and muscle growth characteristics in the pacu (Piaractus mesopotamicus). Pacu eggs were incubated at 25, 27, and 29 degreesC until hatching. After day 5, fish from each temperature were transferred to 5001 tanks. At hatching and after 5, 25, and 60 days, muscle samples were collected, some were frozen in liquid nitrogen and others fixed in 4% paraformaldehyde or 2.5% glutaraldehyde. These samples were used for morphological, histochemical, immunohistochemical, and morphometric analysis. At hatching, we observed a superficial monolayer of small diameter fibers, lying just beneath the skin surrounding several round cells. From day 5, we observed two distinct populations of muscle fibers distributed in two layers: (1) red-in a superficial region with aerobic activity, and following acid preincubation, high mATPase activity, and 2) white-with anaerobic activity, and following alkaline preincubation, high mATPase activity. Twenty-five days after hatching, an intermediate layer and cell proliferating zones could be seen in the dorsal fin muscle region, with intermediate characteristics. Throughout the experimental period, there was an increase in muscle mass due to new fiber recruitment in the cell proliferating zones and between the more differentiated fibers in red, intermediate, and white muscles. This was more obvious from day 25, and at 29 degreesC than at 25 and 27 degreesC. Fiber hypertrophy occurred from hatching to 60 days and was more evident from 5 to 25 days. The number of proliferating nuclei (PCNA-labelling) increased from hatching to 60 days, and was more obvious in the 29 degreesC group at 60 days. Our results show that at incubation temperatures of 25, 27 and 29 degreesC, hypertrophy was predominantly from hatching to 25 days, after that muscle growth by hyperplastic mechanism increased. The interaction of muscle hypertrophic and hyperplastic growth processes in the 29 degreesC group produced the largest fish at the end of the experiment. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: morphology; muscle growth; temperature; Piaractus mesopotamicus